Offshore geotechnical engineering : principles and practice - Dean, E. T. R. (Thomas Telford, 2010)
With activity in the engineering of offshore structures increasing around the world, this book offers an introduction to many of the core design and assessment skills required of those working in the sector, in accordance with the latest codes and standards.
Keywords: Offshore structures.; Ocean engineering.; elektronické knihy; electronic books